Evaluation of Touchable 3D‐Printed Replicas in Museums. (18th January 2018) - Wilson, Paul F.; Stott, Janet; Warnett, Jason M.; Attridge, Alex; Smith, M. Paul; Williams, Mark A.
Abstract: The multisensory aspect of the museum, while neglected for many years, is undergoing a resurgence as museum workers have begun to push towards re‐establishing the senses as a major component of museum pedagogy. However, for many museums a major roadblock lies in the need to conserve rare objects, a need that prevents visitors from being able to interact with many objects in a meaningful way. This issue can be potentially overcome by the rapidly evolving field of 3D printing, which allows museum visitors to handle authentic replicas without damaging the originals. However, little is known about how museum visitors consider this approach, how they understand it and whether these surrogates are welcome within museums. A front‐end evaluation of this approach is presented, finding that visitors were enthusiastic about interacting with touchable 3D printed replicas, highlighting potential educational benefits among other considerations. Suggestions about the presentation of touchable 3D printed replicas are also discussed.